Local government officers 1980 - Strömberg, Lars (University of Gothenburg, 1994)
This survey forms part of the project ´Local government - an evaluation of the reform of amalgamation of municipalities´. In this study the local government officers are studied with regard to background: social background, education, professional experience; work assignments: planning, decision, execution; and attitudes: toward work, the role of the local government administration, connections with politicians, democracy and local autonomy, conflicts, present and future local government policy. The survey also want to shed light on the part the local government officer plays in the decision-making process in different types of municipalities. Changes of this role in connection with the growth of staff of officers and explanations of why these changes take place. Effects of these eventual changes on the possibilities to local political management and control.

Undersökningen studerar de kommunala tjänstemännens sociala bakgrund, utbildning, arbetslivserfarenhet och arbetsuppgifter (beredning, beslut, verkställighet). Frågor ställdes om attityder till arbetet, förvaltningens roll, relationen till politiker, demokrati och självstyrelse, makt, konflikter, samt aktuell och framtida politik. Studien vill också visa vilken roll tjänstemännen spelar för beslutsfattandet i olika kommuntyper, om denna roll har förändrats med tjänstemannakårens tillväxt och vad som i så fall förklarar denna förändring, samt vilka effekter eventuella förändringar har fått för möjligheten till lokal politisk styrning och kontroll.
Undersökningen ingår som en delstudie i forskningsprogrammet 'Den kommunala självstyrelsen - en utvärdering av kommunindelningsreformen'.
Kommunala tjänstemän 1980
Keywords: Working conditions; Arbetsförhållanden; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap